Uso de dados reais para interpretação de gráficos estatísticos sobre função exponencial - Dorigon, Graziela Francheschini (2023)
The present study addresses the use of real data for the interpretation of statistical graphs on an exponential function, exploring the tripod of statistical literacy, real data and problem solving, seeking to answer the following problem: how to develop statistical literacy for interpreting graphs involving an exponential function on high school students using real data? Its general objective was to model, develop, apply and evaluate an educational product for the interpretation of exponential function graphs from real data. To this end, it began by exploring models applied in health, such as those applied to the dissemination of pathogenic organisms among the population, such as the Sars-Cov2 virus. Exploring other applications of the mathematical model, he also investigated the field of biology, in the prey and predator relationship, and in financial mathematics, when he analyzed the performance of cryptocurrencies. He based his reflections on the premise that Mathematics, as recommended by the National Common Curricular Base, should be focused on solving real problems, which highlights its importance in school education. Thus, we sought to analyze the guidelines in this document regarding problem solving based on real data, statistical literacy and the use of technology as a teaching tool. The reflections find support in Vygotsky and the theory of socio-interactionism. The field study was carried out through the creation, development and application of an educational product exploring the tripod presented. The educational product consisted of the creation of a website, focusing on exponential functions, and its application occurred through the development of a didactic sequence applied to students in the first year of high school, at a public school located in the municipality of Soledade, North region of Rio Grande do Sul. The treatment of the collected data occurred in a qualitative and quantitative way, based on the assumptions of Bardin's content analysis, using the NVivo software; the sources of analysis were texts resulting from the transcription of meetings, reporting the application of the didactic sequence and the evaluation of students. The submission of texts to the software generated four categories of analysis: student difficulty, student protagonism, Mathematics and exponential functions and educational product and didactic sequence. The results obtained allowed us to conclude the effectiveness of the relationship between statistical literacy, real data and problem solving in the teaching of Mathematics. The educational product is available on the program website, on the PPGECM educational products portal and on the EduCapes portal https://educapes.capes.gov.br/handle/capes/742159.